Financial sector reforms, economic growth, and stability : experiences in selected Asian and Latin American countries - Faruqi, Shakil 1942-; Bery, Suman K.; Economic Development Institute (Washington, D.C.); World Bank. (Washington, D.C. : World Bank, 1994)
"Compares financial sector reforms and their impact on economic growth and stability in selected countries of Latin America and Asia. Articles range from the quite specific (e.g., securities regulation in Thailand), to more general"--Handbook of Latin American Studies, v. 57.
"Papers prepared for a senior policy seminar held in February 1993 at Bali, Indonesia"--Foreword.
Includes bibliographical references.
Zahid
Keywords: Financial institutions -- Government policy -- Asia -- Congresses; Financial institutions -- Government policy -- Latin America -- Congresses; Banks and banking -- State supervision -- Asia -- Congresses; Banks and banking -- State supervision -- Latin America -- Congresses; Monetary policy -- Asia -- Congresses; Monetary policy -- Latin America -- Congresses